Citizen Reaction to Public Officials, 1969 - Jacob, Herbert ([Verlag nicht ermittelbar], 1984)
This study explored Milwaukee, Wisconsin, respondents' use of and opinions about various government agencies. Part 1, Main File, contains general attitudinal information such as satisfaction with schools, the police, public facilities, and government officials, as well as filter items indicating the respondents' contact with specific agencies. Those interviewees who had used the services of one or more of 50 listed agencies or programs were asked a supplementary set of questions about these particular contacts, focusing on the respondents' views of the treatment received as compared to their expectations. This information is included in Part 2, Supplementary File, which contains a record for each agency. The record was left blank if the agency's services were not used by the respondent.